Peningkatan Profesionalisme Guru Pendidikan Agama Katolik dalam Pengembangan Bahan Ajar Lembar Kerja Siswa (LKS) Melalui Supervisi Klinis Pengawas di Sekolah Dasar Binaan Kota Mataram - Maksimilianus Naben (Jurnal Paedagogy, 2022)
This study aims to increase the professionalism of Catholic religious education teachers in the development of student worksheets (LKS) teaching materials through clinical supervision of supervisors at the elementary schools built in the city of Mataram. This research method uses Supervision Action Research (PTKp). The subjects of this research were 17 teachers of Catholic religious education in the target area of Mataram city. The research instrument used a questionnaire and an observation sheet. The data collected were analyzed qualitatively and quantitatively. The results of this study indicate that coaching in an effort to increase the professionalism of Catholic religious education teachers in developing teaching materials for the preparation of Student Worksheets (LKS) through clinical supervision by supervisors shows a significant increase in each cycle. In addition, the activities in each coaching show that all Catholic religious education teachers can increase their professionalism in every aspect.